SISTEM MONITORING KENYAMANAN TOILET BERBASIS IoT MENGGUNAKAN PLATFORM BLYNK - Parlaungan S., Timbo Faritcan; Novianti, Wieke; Permana, Eka; Ahmad, Hermansyah Nur (Jurnal Teknologi Informasi dan Komunikasi, 2024)
The purpose of this research can monitor and control the comfort of IoT-based toilets (Internet Of Things) using the Blynk Platform. In general, the comfort of the toilet is known if the situation is dirty and seen directly, especially if it causes an unpleasant odor. This system aims to collect temperature, gas data and provide access to toilet condition information to cleaners easily and quickly through an application integrated with Blynk. In monitoring comfort in toilets, the research methods used include literature surveys to understand IoT concepts and relevant technologies, as well as a review of temperature and gas sensor technologies that are suitable for data collection. In addition, user needs analysis and system design are also carried out to ensure the availability of accurate and relevant information. From the results obtained, it is hoped that this study can help determine the condition of the toilet in realtime so that toilet comfort is more awake and users feel comfortable when using the toilet. This research can also be a reference for future researchers related to the material used.